Kajian Potensi Pendidikan Formal Animasi di Sekolah Menengah Kejuruan Kota Cimahi 2011 - Mohammad Rizaldi; Intan R. Mutiaz; Iman Sujudi (ITB Journal Publisher, LPPM ITB, 2013)
Explanation of PP No.28 of 2008 related to the National Industrial Policy (KIN) sets Cimahi city as a base of animation industry development and as a leading sector in the field of animation, film and ICT. Vocational high school animation rated by industry experts is quite attractive but less in terms of competence and result qualities. This study reveal the lack of competence of animation education at vocational high school level in Cimahi based on quality parameters of the drawing test from students sketch presentations. Therefore, to improve its potentials, a formulated education strategy and student entry test based on drawing is needed followed with refining other educational process.